Avaliação da taxa de concepção de novilhas e vacas (Bos taurus x Bos indicus) com o uso de sêmen sexado na inseminação artificial ou embriões produzidos in vivo e in vitro - Peres, Anelise Ribeiro [UNESP] (2014)
The reproduction biotechnologies are used as an alternative to improve reproductive efficiency and accelerate the production of animals of high performance zootechnical. This study aimed to evaluate the conception rate of heifers and cows crossbred inseminated with sexed semen and conventional (Experiment 1) and conception rate of heifers and cows crossbred receiving the transfer of embryos produced in vivo (TE) and in vitro (PIVE) with sexed semen (Experiment 2). In experiment 1, sexed and conventional semen were used for the insemination of cows (n = 50) and heifers (n = 50) after 18-24 hours of estrous observation; in experiment 2 embryos produced in vivo (n = 40) and in vitro (n = 50) were transferred to cows (n = 45) and heifers (n = 45). Animals inseminated with sexed semen showed conception rate from 44% (11/25) for cows and 52% (13/25) for heifers and with conventional semen, the conception rate was 72% (18/25) for cows and 68% (17/25) for heifers. The conception rate obtained by the technique of in vitro production of embryos was 24% (6/25) for cows and 28% (7/25) for heifers and for embryos produced in vivo was 45% (9/20) both for cows as for heifers. The technique of AI with sexed semen presented statistical difference (p <0.05) when compared with conventional semen, but animal category was not statistically different (p> 0.05) (Experiment 1). No statistical difference (p> 0.05) between the production techniques in vivo and in vitro embryo or between animal category was observed. The results indicate that the interval between estrous observation and insemination 18-24 hours was effective on conception of both cows and heifers using conventional and sexed sêmen, however to approximate of the results obtained by the conventional semen is no need to most research to improve conception rates with sexed semen (Experiment 1). Conception rates with embryos PIVE in heifers and cows recipients were lower than those produced in ...